Inhibition of the late sodium current as a potential cardioprotective principle: effects of the late sodium current inhibitor ranolazine. (14th June 2006) - Belardinelli, L; Shryock, J C; Fraser, H
Abstract : Pathological conditions linked to imbalances in oxygen supply and demand (for example, ischaemia, hypoxia and heart failure) are associated with disruptions in intracellular sodium ([Na + ]i ) and calcium ([Ca 2+ ]i ) concentration homeostasis of myocardial cells. A decreased efflux or increased influx of sodium may cause cellular sodium overload. Sodium overload is followed by an increased influx of calcium through sodium-calcium exchange. Failure to maintain the homeostasis of [Na + ]i and [Ca 2+ ]i leads to electrical instability (arrhythmias), mechanical dysfunction (reduced contractility and increased diastolic tension) and mitochondrial dysfunction. These events increase ATP hydrolysis and decrease ATP formation and, if left uncorrected, they cause cell injury and death. The relative contributions of various pathways (sodium channels, exchangers and transporters) to the rise in [Na + ]i remain a matter of debate. Nevertheless, both the sodium-hydrogen exchanger and abnormal sodium channel conductance (that is, increased late sodium current (INa )) are likely to contribute to the rise in [Na + ]i . The focus of this review is on the role of the late (sustained/persistent) INa in the ionic disturbances associated with ischaemia/hypoxia and heart failure, the consequences of these ionic disturbances, and the cardioprotective effects of the antianginal and anti-ischaemic drug ranolazine. Ranolazine selectively inhibits late INa, reduces [Na + ]i -dependent calcium overload and attenuates the abnormalities of ventricular repolarisation and contractility that are associated with ischaemia/reperfusion and heart failure. Thus, inhibition of late INa can reduce [Na + ]i -dependent calcium overload and its detrimental effects on myocardial function.